2022
DOI: 10.3390/cancers14153657
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Physical Activity during and after Thyroid Cancer Treatment on Fatigue and Quality of Life: A Systematic Review

Abstract: Background: Several epidemiological studies have provided evidence of the usefulness of physical activity for cancer prevention, increased survival and quality of life (QoL), but no comprehensive review is available on the effects on thyroid cancer. The present systematic review provides an overview of the effects of physical activity on fatigue, QoL and health-related quality of life (HRQoL) in patients with thyroid cancer diagnosis both during and after treatment, with a focus on sex. Methods: A literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Different studies have demonstrated the positive impact of physical exercise on several outcomes in thyroid cancer survivors. These include improvements in physical fitness, fatigue reduction, and enhanced overall quality of life [ 19 , 20 , 41 ]. Additionally, physical exercise has been associated with lower recurrence rates, decreased mortality, and improved long-term survival outcomes in cancer survivors [ 42 , 43 ].…”
Section: Physical Exercise and Rehabilitationmentioning
confidence: 99%
“…Different studies have demonstrated the positive impact of physical exercise on several outcomes in thyroid cancer survivors. These include improvements in physical fitness, fatigue reduction, and enhanced overall quality of life [ 19 , 20 , 41 ]. Additionally, physical exercise has been associated with lower recurrence rates, decreased mortality, and improved long-term survival outcomes in cancer survivors [ 42 , 43 ].…”
Section: Physical Exercise and Rehabilitationmentioning
confidence: 99%